2020
DOI: 10.3390/ma13204688
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Osseous Defects after Mandibular Third Molar Removal with a Resorbable Alloplastic Grafting Material: A Case Series with 1- to 2-Year Follow-Up

Abstract: Mandibular third molar (M3) surgical extraction may cause periodontal complications on the distal aspect of the root of the adjacent mandibular second molar (M2). Patients older than 26 years with periodontal pathology on the distal surface of the M2 and a horizontal/mesioangular impacted M3 may benefit from bone regenerative therapy at the time of surgery. In this prospective case series, an alloplastic fully resorbable bone grafting material, consisting of beta-tricalcium phosphate (β-TCP) and calcium sulfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…At the end of the 12-months follow-up, the PPD was 3.1 ± 0.4 mm vs. 7.5 ± 0.7 mm (baseline) for grafted sites and 4.8 ± 0.5 mm vs. 7.8 ± 0.8 mm for the nongrafted sites, with a bone gain of 3.59 mm for grafted sites against 1.20 mm for nongrafted sites. Leventis et al [40], in a case series with a mean follow-up of 1.5 years, investigated the combined use of beta-tricalcium phosphate and calcium sulfate in post-extractive sockets of M3 in patients with preexisting periodontal pockets distal to M2. At the end of the follow-up period, the authors found a mean PPD of 2.00 ± 0.71 mm and a radiographic bone gain of 6.07 ± 0.28 mm distal to M2.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the 12-months follow-up, the PPD was 3.1 ± 0.4 mm vs. 7.5 ± 0.7 mm (baseline) for grafted sites and 4.8 ± 0.5 mm vs. 7.8 ± 0.8 mm for the nongrafted sites, with a bone gain of 3.59 mm for grafted sites against 1.20 mm for nongrafted sites. Leventis et al [40], in a case series with a mean follow-up of 1.5 years, investigated the combined use of beta-tricalcium phosphate and calcium sulfate in post-extractive sockets of M3 in patients with preexisting periodontal pockets distal to M2. At the end of the follow-up period, the authors found a mean PPD of 2.00 ± 0.71 mm and a radiographic bone gain of 6.07 ± 0.28 mm distal to M2.…”
Section: Discussionmentioning
confidence: 99%
“…The osteoimmunological process involves several signalling pathways and cell-to-cell communications mediated by growth factors, including platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), and cytokines. Fibroblasts and macrophages replace the fibrin matrix with granulation tissue during the maturation phase of wound healing [36][37][38][39] Platelets and leukocytes, therefore, play a crucial role in all stages of wound healing, from coagulation to angiogenesis and activation of cells (e.g., monocytes, neutrophils, fibroblasts macrophages, and mesenchymal stem cells) that are involved in tissue regeneration (Table 3).…”
Section: Cell Proliferation Phasementioning
confidence: 99%
“…The Osteology Foundation 6th Expert Meeting (2011) concluded that the potential benefit of socket preservation therapies using different protocols was demonstrated, resulting in significantly less vertical and horizontal contraction of the alveolar bone crest [78]. Leventis et al (2014Leventis et al ( , 2016Leventis et al ( , 2018Leventis et al ( , 2020 reported that grafting of extraction sockets without primary wound closure can be an effective method of preserving the contour and architecture of the alveolar ridge using a minimally invasive tooth removal and SA technique using a novel self-hardening β-tricalcium phosphate bone substitute graft material (Ethoss ® ) [79]. At re-entry for implant placement, bone core biopsies were obtained, and primary implant stability was measured by final seating torque and resonance frequency analysis.…”
Section: Comparative Study Analysis Of Socket Augmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Một số nghiên cứu cho thấy khiếm khuyết nha chu bao gồm sự mất bám dính lâm sàng, gia tăng độ sâu túi nha chu, thiếu hổng xương ổ ở phía xa răng 7 được cho là xuất hiện và tồn tại dai dẳng sau khi nhổ răng khôn hàm dưới có góc độ nghiêng gần [3], [4]. Nghiên cứu của Kugelburg và cộng sự (1990) cho thấy các bệnh nhân sau nhổ răng được theo dõi trong 2 năm cho kết quả 43,3% có độ sâu túi (PD) vượt quá 7mm và 32,1% cho thấy khiếm khuyết xương ổ ở phía xa răng 7 vượt quá 4 mm [5], [6].…”
Section: đặT Vấn đềunclassified